ENHANCING SECRETARIES' PRESENTATION SKILLS USING NLP TECHNIQUES WITH SENSORY REPRESENTATION SYSTEMS - Niken Yolanda; Inayah Safani, Rita Hartati (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research examines the impact of Neuro-Linguistic Programming (NLP) techniques, particularly sensory representation systems, on enhancing secretaries' presentation skills. In today's fast-paced business environments, secretaries are required to deliver impactful and clear presentations. By applying NLP’s visual, auditory, and kinesthetic (VAK) model, secretaries can tailor their presentations to match the sensory preferences of their audience. The study suggests that utilizing sensory representation systems not only improves audience engagement and retention but also aligns with cognitive and constructivist learning theories, making presentations more effective. This research uses qualitative, literature-based methods to explore the significance of NLP in professional development for secretaries.